Efforts to Improve Skills Overhand Service On Volleyball Games By Using Part and Whole (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2018)
The purpose of this research is to improve the overhead service techniques of volleyball related to Physical Education class in XI C Animation in SMK Negeri 4 Malang by using the method of part and whole. This research is using quantitative and qualitative descriptive approach. This research was also carried out by using two cycles and each cycle consists of four phases: (1) planning, (2) implementation, (3) observation, and (4) reflection. Subjects in this study is a 34 students of XI C class of Animation in SMK Negeri 4 Malang. The success rate of students in the first cycle is 75%, in the second cycle is 87%. Based on the results of the study is by using part and whole method can improve the ability of overhead service techniques on students of XI C class of Animation in SMK Negeri 4 Malang.